The discovery of the rare genus Xyeloblacus van Achterberg, 1997 (Hymenoptera: Braconidae, Blacinae) in China, with description of a new species - Huangfu, Wei-Guo; Chai, Hong-Fei; Chen, Xue-Xin (Zootaxa, 2012)
The Blacinae Foerster, 1862 is a cosmopolitan subfamily of Braconidae (Hymenoptera), with five tribes and 14 genera (van Achterberg 1976, 1988). The genus Xyeloblacus van Achterberg, 1997 is the only member of the tribe Xyeloblacini van Achterberg with two known species in the world (van Achterberg and Altenhofer, 1997; Yu et al., 2005). van Achterberg and Altenhofer (1997) mentioned four important characters for Xyeloblacus as follows: the straight ventral margin of the clypeus, the crenulate anterior subalar depression, the curved vein 1-1A of fore wing, and the presence of vein 2A of hind wing. The members of this genus are parasitoids of Xyela spp. (Xyeloidea: Xyelidae) (van Achterberg and Altenhofer, 1997).